Carbon Neutral China by 2060: The Role of Clean Heating Systems - Chang Su; Frauke Urban (Energies, 2021)
Smog pollution is a severe social and environmental concern for the space-heating regions in China due to fossil-intensive space heating. To reduce polluting emissions and improve social and environmental performance, local government agencies should choose adequate cleaner space-heating technologies based on diverse local conditions. This implies that all cleaner heating solutions should be considered, including low-emissions fossil fuel district heating and low-emissions fossil fuel decentralized heating as transitional technologies, as well as biomass and electricity-driven heat pumps as long-term solutions. However, stakeholders such as policy makers, equipment manufacturers, and house owners, often lack necessary information to assess the feasibility for installing adequate heating solutions at the local level. It is therefore necessary to establish a systematic method to evaluate each heating solution in various geolocations of China. This paper reviews the current heating situation in China and proposes a spatial system analysis method as a tool for heating-solution feasibility evaluation. By applying the spatial system analysis method, a qualitative investigation on the choice of heating solution in different regions of China is provided.